(untitled) (Research, Society and Development, 2022)
Aging is a natural process of life, morphological, functional, biochemical and psychological changes arise that compromise the autonomy of the organism in the face of the external environment, leaving the individual more vulnerable and susceptible to pathologies. This study aimed to present, through the literature, possible fall prevention strategies in the elderly at home. The present study consisted of a descriptive and qualitative research, carried out through a narrative bibliographical review in order to find studies related to the prevention of falls in the elderly and that present strategies for the subject. The searches were carried out through searches on the following scientific platforms: Google Scholar, Lilacs (Latin American and Caribbean Literature in Health Sciences), Scielo (Scientific Electronic Library Online), Virtual Health Library (VHL), in search of articles between the years 2015 and 2022. The research was carried out between May and August 2022. The studies found made it evident that the practice of physical exercises together with sensorimotor stimulation considerably increase the quality of life of the elderly and promote their independence motor. In view of this, it was possible to prove that active elderly people are less susceptible to diseases and do not have motor instability. Physical exercise along with other stimuli promote a better quality of life for the elderly.